1984
DOI: 10.1111/j.1365-2125.1984.tb02497.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acetylator phenotype on the disposition of aminoglutethimide.

Abstract: 1 Aminoglutethimide (AG) 500 mg was administered orally to four normal volunteers and eight patients undergoing treatment for metastatic breast cancer. In each subject the acetylator phenotype was established from the monoacetyldapsone (MADDS)/dapsone (DDS) ratio. 2 Acetylaminoglutethimide (acetylAG) rapidly appeared in the plasma and its disposition paralleled that of AG. 3 A close relationship (P < 0.01) was observed between the acetyl AG/AG and MADDS/DDS ratio suggesting that AG may undergo polymorphic acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
1
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 18 publications
8
1
1
Order By: Relevance
“…However, AUC ratios above 1 have been reported previously (Coombes et aI., 1980(Coombes et aI., , 1982Stuart-Harris et aI., 1985). Our finding of a positive correlation between the initial clearance value of aminoglutethimide and the AUC ratio contrasts with the findings of Adam et al (1984) who reported a significant negative correlation coefficient. During phase I, these 2 patients had the smallest AUC ratios observed.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, AUC ratios above 1 have been reported previously (Coombes et aI., 1980(Coombes et aI., , 1982Stuart-Harris et aI., 1985). Our finding of a positive correlation between the initial clearance value of aminoglutethimide and the AUC ratio contrasts with the findings of Adam et al (1984) who reported a significant negative correlation coefficient. During phase I, these 2 patients had the smallest AUC ratios observed.…”
Section: Discussioncontrasting
confidence: 99%
“…The elimination of this metabolite showed the same elimination rate constant as for aminoglutethimide, suggesting that production is the rate-limiting step in the elimination of this metabolite (Rowland and Tozer, 1980). The AUC ratios between N-acetylaminoglutethimide and aminoglutethimide obtained in the present study (table III) were in accordance with results obtained by Adam et al (1984), but our values showed a larger spread with some especially high values in phase 1. However, AUC ratios above 1 have been reported previously (Coombes et aI., 1980(Coombes et aI., , 1982Stuart-Harris et aI., 1985).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…hydroxylamine is also toxic to human monoDapsone administered at 100 mg acutely has nucleocytes in vitro (Coleman et al, 1989) and often been used as a probe drug for the assessin granulopoiesis in vitro (Weetman et al, 1980). ment of acetylator phenotype (Adam et al, 1984;Horai et al, 1985;Hutchings et al, 1984). Swain et al (1983) noted that after a single dose of 150 mg no patients or volunteers suffered adverse effects.…”
Section: Discussionmentioning
confidence: 99%